(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Diabetes Mellitus (DM) Type 2 is a chronic disease that has become a global health concern, with a rising prevalence, particularly in developing countries such as Indonesia. This disease is frequently linked to an unhealthy lifestyle, including a high-sugar and fat diet, a lack of physical activity, obesity, and genetic factors. Education on the risk prevention of Type 2 Diabetes is crucial to lower the incidence of this disease and its detrimental effects. The purpose of community service is education to reduce the risk and prevalence of Type 2 Diabetes Mellitus through increasing awareness, knowledge, and changes in people’s behavior in living a healthy lifestyle. Method: The educational method is carried out through four stages starting from social educational, process learning, direct practicum and evaluation learning. The service and socialization results aimed at 24 respondents, and the results provided a comprehension of the essential principles, benefits, and advantages of efforts to reduce the risk of DM type 2. The pre-test findings revealed that 58.3% were in the level of lack of knowledge and 42.7% were adequate, while the post-test results showed that 79.2% were extremely knowledgeable and 20.8% were well understood, demonstrating a considerable gain in knowledge. The conclusion of education on the prevention of type 2 diabetes mellitus (DM) emphasizes the necessity of making healthy lifestyle changes to lower the chance of getting the condition. It is envisaged that citizens’ efforts to avoid type 2 diabetes would be more successful, durable, and engage all levels of society.